The Influence of Knowledge Management Towards Employee Work Productivity With Mediation of Competence at PT. Rahayu Perdana Trans - Ranni Dian Octaviana (Universitas Ciputra Surabaya, 2021)
The purpose of this research is to find out the impact of knowledge management towards employee work productivity with mediation of competence at PT. Rahayu Perdana Trans. The method used is quantitative research. The population used in this study were employees of PT. Rahayu Perdana Trans who has the criteria has taken at least a Bachelor's degree (S1) study & already has work experience outside of PT. Rahayu Perdana Trans at least 2years, amounting to 85 people. The data collection technique in this study was carried out by distributing questionnaires using a Likert scale. Based on the results of data analysis, it can be concluded that all existing indicators are valid and reliable so that they have a significant effect.